The effect of vermicompost on growth of shallots (Allium ascalonicum L.) - Lina Maulina; Karnan Karnan; Ahmad Raksun (Jurnal Pijar Mipa, 2023)
Shallots have long been cultivated by farmers intensively because shallots have a high economic value, so they become a source of income for farmers. Shallots are annual plants belonging to monocotyledonous plants that have multi-layered tubers formed from layers of leaves that enlarge and unite with cylindrical leaves. The soil fertility level influences shallots' growth, development, and production, requiring additional fertilizers. One of the good fertilizers used is vermicompost. Vermicompost is an organic fertilizer containing microbes and elements required for plant growth. This study aims to determine vermicompost's effect on shallot growth (Allium ascalonicum L.). This study used a completely randomized design with ten replications. The treatment levels consisted of P0 = 0 grams of vermicompost per 1 kg of soil, P1 = 40 grams of vermicompost per 1 kg, P2 = 80 grams of vermicompost per 1 kg of soil, and P3 = 120 grams of vermicompost per 1 kg of soil. Parameters observed were the number of leaves, number of tubers, plant height, wet weight, dry weight, and chlorophyll content of shallot. The research data were analyzed using ANOVA and Duncan's Multiple Range Test at the 5% level. The results showed that the addition of vermicompost had a significant effect on the number of leaves and chlorophyll content of the shallot but had no significant impact on the number of bulbs, plant height, wet weight, and dry weight of the shallot.